Association between lipoprotein (a) and heart failure with reduced ejection fraction development. Issue 1 (1st December 2021) - Wu, Baoquan; Zhang, Zhiling; Long, Juan; Zhao, Hanjun; Zeng, Fanfang
Abstract: Background: The current study aimed to evaluate the relationship between baseline serum lipoprotein (a) [Lp(a)] level and heart failure with reduced ejection fraction (HFrEF) development. Methods: This was a retrospective study, and participants were enrolled from the outpatient clinic. All data were extracted from the electronic health record of the outpatient clinic system. The follow‐up was performed through reviewing the clinical notes at the outpatient clinic system, and study outcome of the current study was the first diagnosis of HFrEF. Participants were divided into low Lp(a) (<30 mg/dl, n = 336) and high Lp(a) (≥30 mg/dl, n = 584) groups. Results: Individuals in the high Lp(a) group were more likely to be men and have diabetes mellitus (DM) and dyslipidemia. Increased Lp(a) at baseline was positively associated with serum N‐terminal pro‐B natriuretic peptide level while negatively associated with left ventricular ejection fraction (LVEF) at follow‐up. After adjusting for covariates, per 10 mg/dl increase in baseline Lp(a) remained significantly associated with HFrEF, with odds ratio of 1.17 (95% confidence interval of 1.05, 1.46). The magnitude of association between baseline Lp(a) level and HFrEF was greater in men and in individuals with DM or coronary heart disease (CHD), while it was weaker in individuals treated with beta‐blocker at baseline. Conclusion: Increased Lp(a) at baseline was associated with HFrEF development. The adverse effects of Lp(a) were greater on men and individuals with DM or CHD, which were mitigated by beta‐blocker therapy. These findings together underscore the possibility and usefulness of Lp(a) as a new risk factor to predict HFrEF. Abstract : After stepwise adjusting for covariates, per 10 mg/dl increase in baseline Lp(a) remained significantly associated with HFrEF, with odds ratio of 1.17 (95% CI 1.05, 1.46). In addition, the magnitude of the association between baseline Lp(a) level and HFrEF was greater in men and in individuals with diabetes mellitus (DM) or coronary heart disease (CHD), while it was weaker in individuals treated with beta‐blocker at baseline.